Cauchy's functional equation in restricted complex domains - Watcharapon Pimsert; Vichian Laohakosol; Sajee Pianskool (International Journal of Mathematics and Mathematical Sciences)
Using a method modified from that used by Pisot and Schoenberg in 1964-1965, a Cauchy's functional equation with restricted domains in the complex field is solved for uniformly continuous solutions.